2016
DOI: 10.1001/jamafacial.2016.0107
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Aesthetic Outcome of Linear vs Multiple Z-Plasty Scars in a National Survey

Abstract: IMPORTANCEThe process of Z-plasty scar revision breaks up a linear scar into multiple parts with the purpose of camouflage and improvement of the cosmetic appearance of surgical scars. Although this postulation guides the practices of many reconstructive surgeons, few studies support improved aesthetic outcomes.OBJECTIVE To compare the perceived cosmetic appearance of linear scars vs zigzag scars by the general public. DESIGN, SETTING, AND PARTICIPANTSA computer-generated image of a mature scar was designed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Some studies have found that the W‐plasty technique is significantly better than SL resection, and other studies have shown that there is no statistical difference between the two methods of skin closure. 4 , 8 , 9 In our previous study, we confirmed that the technique of CTR with a tension offloading device could effectively decrease the tension across the surgical incision and significantly reduce the keloid recurrence rate and achieve therapeutic efficacy. 13 In the research presented here, we first introduce the concept of CTR into traditional W‐plasty, aiming to overcome the drawbacks of using W‐plasty technology alone.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Some studies have found that the W‐plasty technique is significantly better than SL resection, and other studies have shown that there is no statistical difference between the two methods of skin closure. 4 , 8 , 9 In our previous study, we confirmed that the technique of CTR with a tension offloading device could effectively decrease the tension across the surgical incision and significantly reduce the keloid recurrence rate and achieve therapeutic efficacy. 13 In the research presented here, we first introduce the concept of CTR into traditional W‐plasty, aiming to overcome the drawbacks of using W‐plasty technology alone.…”
Section: Discussionsupporting
confidence: 59%
“…W-plasty has achieved good clinical results, especially in patients with scars not aligned to an RSTL on curved surfaces, because many small segments of the Wplasty do run parallel with RSTLs and broken-line scars are easily accepted by the human eye. 7,8 Previous studies have shown that the W-plasty technique demonstrates a better mean scar appearance compared with straight-line (SL) closure. 9 W-plasty redirects the forces of contracture, converting the lines of distraction from perpendicular to oblique and relieving the bowstringing effect of linear scars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with facial skin cancers returning for follow-up after MMS were asked to rate their postoperative scar appearance at their 1-to-2-week and 3-month visits using the Patient and Observer Scar Assessment Scale (POSAS). 9,10 The POSAS has multiple components, but for this study, only the "overall opinion" scale was used. Scoring was performed on a scale of 1 to 10, where 1 is synonymous with "like normal skin" and 10 to the "worst scar imaginable," such that higher scores represent a worse perception of scar appearance.…”
Section: Methodsmentioning
confidence: 99%
“…12,48,49,53 Ratnarathorn et al reported that the participants of their study preferred the appearance of linear scars to irregular scars created by Z-plasty. 57…”
Section: Z-plastymentioning
confidence: 99%